2022
DOI: 10.1029/2021wr031888
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of Seasonal Cropland Abandonment on Evapotranspiration and Water Resources in the Humid Lowland Region, Southern China

Abstract: The rotation between rice and winter rape (Brassica napus L.) system is widely distributed around the world especially in southern China (Frolking et al., 2002;S. Liu et al., 2010;M. Zhou et al., 2014), supplying us with food and raw materials for edible oil. Evapotranspiration (ET) is a key hydrological process, which closely links the Earth's energy and water cycles (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…In comparison, the regression relation between AET and T was the best, followed by Rs and the lowest of P, with an adjusted R 2 of 0.95, 0.88, and 0.61, respectively. It showed that AET in the TGRA was mainly affected by the temperature and radiation term, which is consistent with the conclusion of Yan et al [53].…”
Section: Correlation Analysissupporting
confidence: 91%
“…In comparison, the regression relation between AET and T was the best, followed by Rs and the lowest of P, with an adjusted R 2 of 0.95, 0.88, and 0.61, respectively. It showed that AET in the TGRA was mainly affected by the temperature and radiation term, which is consistent with the conclusion of Yan et al [53].…”
Section: Correlation Analysissupporting
confidence: 91%
“…For investigating how the variation of CDHW events can be attributed to variations of its influencing factors, we employ path analysis to explore the response of CDHW events to the temperature and the WDI (i.e., difference between precipitation and PET), of which the selected two drivers are the most critical factors influencing CDHW events (Tomas‐Burguera et al., 2020; Y. Zhang, Hao, et al., 2022). Path analysis is an extension of multiple regression method that accounts for the covariance among variables, which has been widely applied to estimating the magnitude and significance of hypothesized causal connections between dependent and independent variables, when the effects of the variables are confounded (Saito et al., 2009; Smith et al., 1997; Yan et al., 2022). It has the superior advantage of decomposing the correlation coefficient into direct and indirect interaction coefficients, that is, direct path coefficient and indirect path coefficient relative to the commonly used regression method (Cheng et al., 2021; B. Zhang et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Zhang, Hao, et al, 2022). Path analysis is an extension of multiple regression method that accounts for the covariance among variables, which has been widely applied to estimating the magnitude and significance of hypothesized causal connections between dependent and independent variables, when the effects of the variables are confounded (Saito et al, 2009;Smith et al, 1997;Yan et al, 2022). It has the superior advantage of decomposing the correlation coefficient into direct and indirect interaction coefficients, that is, direct path coefficient and indirect path coefficient relative to the commonly used regression method (Cheng et al, 2021;B.…”
Section: Statistical Analysis Methodsmentioning
confidence: 99%
“…Traditional field survey and measurement methods are time-consuming, laborious, costly, and easily affected by the natural environment, making it difficult to obtain data [21]. Simultaneously, the accuracy and representativeness of field-collected data also face challenges including subjectivity and spatial limitations [22]. In contrast, using remote sensing technology to obtain cropland monitoring data shows advantages.…”
Section: Introductionmentioning
confidence: 99%